2019
DOI: 10.1016/j.sjbs.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilizing rhizobacteria as alternative of chemical fertilizer for growth and yield of Triticum aestivum (Var. Galaxy 2013)

Abstract: AimThe presence of Phosphorus as a macronutrient in soil is necessary for plant growth and its deficiency restricts crop yield. Therefore, the aim of current study is to isolate promising rhizospheric phosphate solubilizing bacteria presenting with plant growth promoting (PGP) traits and their utilization as biofertilizers to improve Triticum aestivum (Var. Galaxy 2013) growth and nutrition.MethodOut of 30 isolates obtained from rhizosphere of various plants of different regions, 10 best PSRB strains (WumS-3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
5
26
0
3
Order By: Relevance
“…For plants inoculated with PSB 5 (exhibiting the highest PSC), the lower rhizosphere available P fraction may partly be attributed to important RDW and root depth that indicate an important root growth presumably responsible for increased root P uptake and P content in wheat shoots (Table 4). In line with these findings, experimental evidences about soil bacterial P bio-solubilization are available (Mamta et al, 2010;Batool and Iqbal, 2019;Emami et al, 2019), meanwhile relationship between PSB and root functional traits and their extension within the rhizosphere are not yet fully deciphered and so more when it comes more particularly to temporal variations throughout crop growth stages. Overall, our findings show for the first time that PSB may exhibit different PSC over growing time (three plant growth stages) and that P solubilization rate at the rhizosphere level likely difficult to estimate while roots continue to grow spatially and temporally.…”
Section: P Solubilizing Bacteria May Have Greater Effect On Rooting Smentioning
confidence: 95%
“…For plants inoculated with PSB 5 (exhibiting the highest PSC), the lower rhizosphere available P fraction may partly be attributed to important RDW and root depth that indicate an important root growth presumably responsible for increased root P uptake and P content in wheat shoots (Table 4). In line with these findings, experimental evidences about soil bacterial P bio-solubilization are available (Mamta et al, 2010;Batool and Iqbal, 2019;Emami et al, 2019), meanwhile relationship between PSB and root functional traits and their extension within the rhizosphere are not yet fully deciphered and so more when it comes more particularly to temporal variations throughout crop growth stages. Overall, our findings show for the first time that PSB may exhibit different PSC over growing time (three plant growth stages) and that P solubilization rate at the rhizosphere level likely difficult to estimate while roots continue to grow spatially and temporally.…”
Section: P Solubilizing Bacteria May Have Greater Effect On Rooting Smentioning
confidence: 95%
“…Plates were incubated at 37 ± 2 °C for 48 h. Salt tolerance was determined in terms of (MIC) of salt. Salt tolerant bacterial strains were further checked for their drought tolerance and PGP traits like IAA, siderophore and HCN production as describe earlier ( Batool and Iqbal, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…60 studied on Phosphate solublization in the National Botanical Research institutes on phosphate growth medium (NBRIP) and found that the concentration of soluble phosphate ranged between 101.91 µg/ml and 174.33 µg/ml. 61 also studied on the solubilization of TCP and found that the soluble phosphate concentration was ranged from 41.20 to 119.95 µg/ml in the NBRIP medium. The better performance of AAUFE29 (Enterobacter sp.V.H.18) to release the available phosphorus in PVK medium indicates the role played by insoluble phosphate sources to trigger microbial action.…”
Section: Discussionmentioning
confidence: 99%